Mandasuchus tanyauchen, gen. et sp. nov., a pseudosuchian archosaur from the Manda Beds (?Middle Triassic) of Tanzania. (29th November 2017) - Butler, Richard J.; Nesbitt, Sterling J.; Charig, Alan J.; Gower, David J.; Barrett, Paul M.
ABSTRACT: The diverse assemblage of extinct archosaur species known from the Manda Beds of Tanzania has provided key insights into the timing and tempo of the early part of the archosaur radiation during the Middle Triassic. Several archosaur specimens were collected from the Manda Beds in 1933 by F. R. Parrington, and three of these were subsequently described and made the basis of a new genus, ' Mandasuchus, ' in a 1956 doctoral dissertation. However, this important fossil material was never formally published, and >60 years later ' Mandasuchus ' and ' Mandasuchus tanyauchen ' remain nomina nuda, despite frequent references to them in the literature. Here, we provide a detailed description of this material, provide the first formal diagnosis of Mandasuchus tanyauchen, gen. et sp. nov., and assess its phylogenetic position. The holotype of M. tanyauchen includes a well-preserved partial postcranial skeleton and fragmentary cranial remains. Four referred specimens include two partial skeletons, consisting primary of postcranial remains, a partial maxilla that was previously assigned to the dinosaur clade Saurischia, and a well-preserved astragalus and calcaneum that may belong to the holotype individual. Mandasuchus tanyauchen is diagnosed by a unique combination of character states, as well as by two possible autapomorphies (ascending process of maxilla thin and compressed from anterolateral to posteromedial; femur with distinct pit lateral to the distal-most expression of the posteromedial tuber). Our phylogenetic analysis recovered M. tanyauchen within Paracrocodylomorpha, as the sister taxon to all other sampled members of Loricata. http://zoobank.org/urn:lsid:zoobank.org:pub:7DA9AF92-9365-4200-AE19-C7D6AE4C4966 SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Butler, R. J., S. J. Nesbitt, A. J. Charig, D. J. Gower, and P. M. Barrett. 2018. Mandasuchus tanyauchen, gen. et sp. nov., a pseudosuchian archosaur from the Manda Beds (?Middle Triassic) of Tanzania; pp. 96–121 in C. A. Sidor and S. J. Nesbitt (eds.), Vertebrate and Climatic Evolution in the Triassic Rift Basins of Tanzania and Zambia. Society of Vertebrate Paleontology Memoir 17. Journal of Vertebrate Paleontology 37(6, Supplement).